Analisis Penyusunan Laporan Keuangan Usaha Mikro Kecil Dan Menengah Berdasarkan SAK UMKM - Febby Ayu Silvia Br Sitepu (Jurnal Mahkota Bisnis (Makbis), 2022)
This study aims to provide an overview of the preparation of financial statements made by MSMEs based on their conformity with SAK and explain the obstacles faced in their application. The object of this research is CV. Putra Main Temple. This research is a descriptive qualitative research using a case study approach. Data was collected through interviews. The results showed that the financial statements of CV. Candi Utama Putra is still not in accordance with SAK UMKM. Then, the information in the financial statements is still simple and still uses a cash basis even though the owner has received training in preparing financial statements from practitioners. Constraints faced by owners in making financial statements are the lack of time allocation they have and the assumption that making financial statements is complicated and difficult for owners to understand